In Harm's Way? The Effect of Disasters on the Magnitude and Location of Low‐Income Housing Tax Credit Allocations. (1st February 2022) - Brennan, Mark; Mehta, Aditi; Steil, Justin
Abstract: This paper analyzes the effect of disasters on affordable housing construction. Exploiting the exogenous timing of disasters and 26 years of affordable housing data, we derive causal estimates of the effect of severe floods on county‐level Low‐Income Housing Tax Credit (LIHTC) allocations nationwide. We find that states respond to severe floods by increasing the number of LIHTC units per capita allocated to a flood‐struck county by 57 percent in the year after the disaster, compared to other years. We argue that this increased allocation of LIHTC units is indicative of a process of institutional or policy conversion, in which states are repurposing the three‐decade‐old housing tax credit program to meet contemporary disaster assistance and recovery needs. Given that the LIHTC program was not designed with disasters in mind, do the new units ameliorate or exacerbate renters' exposure to disaster risk? We find that severe floods are associated with a significant increase in LIHTC units per capita allocated outside of the 500‐year floodplain in an affected county within the three years after a severe flood. These findings suggest that states and housing developers are using the LIHTC program to support disaster recovery by expanding subsidized rental options in disaster‐struck counties and ameliorating risk to low‐income renters by locating those units outside of floodplains.